Aerosol generation during pulmonary function testing: Monitoring during different testing modalities. Issue 4 (28th July 2022) - Wu, Joyce K.Y.; Ryan, Clodagh M.; Hiebert, Ryan J.; Han, Ziwen; Liu, Annie; Jeong, Cheol-Heon; Mubareka, Samira; Evans, Greg J.; Chow, Chung-Wai
Abstract: Rationale: Severe acute respiratory syndrome caused by coronavirus 2 (SARS-CoV-2) was declared a pandemic on March 11, 2020. Countries entered lockdown, restricting medical activities to essential services. Pulmonary function tests (PFT) are crucial for management of lung diseases. With limited data regarding aerosol generation and the risk of disease transmission during PFTs, many laboratories closed. Our objective is to quantify aerosol generation during different PFT modalities. Methods: We measured aerosol particles in the 0.3-10.0 µm range with an Optical Particle Sizer (Model 3330; TSI Incorporated) and collected bioaerosols to detect respiratory pathogens during clinically indicated PFTs at a hospital-based laboratory during 2 time points in 2020. Results: We monitored 81 and 41 individual multi-modality PFT sessions in June/July and December, respectively. Slow vital capacity, forced vital capacity and diffusion capacity generated higher aerosol counts compared to pre- and post-test room levels although all modalities were lower than during talking or coughing. The aerosol sizes generated were primarily 2.5-10 µm. Oscillometry generated higher overall concentrations than room sampling, also primarily in the 2.5-10 µm aerosols. The bioaerosol filters revealed no respiratory viruses or bacteria. Conclusions: While PFT can generate aerosols, it is less than normal speech with the exception of PFT-induced coughing. Our findings suggest the risk of SARS-CoV-2 transmission is not increased and support the re-opening of PFT laboratories that adhere to universal masking, use of personal protective equipment and stringent infection control protocols. We strongly endorse adherence to public health guidelines in the operation of PFT laboratories.